Acute and chronic pseudo-obstruction: a current update - Bernardi, Maria-Pia; Warrier, Satish; Lynch, A. Craig; Heriot, Alexander G. (ANZ journal of surgery, 2015)
Acute colonic pseudo‐obstruction (ACPO) and chronic intestinal pseudo‐obstruction (CIPO) are distinct clinical entities in which patients present similarly with symptoms of a mechanical obstruction without an occlusive lesion. Unfortunately, they also share the issues related to a delay in diagnosis, including inappropriate management and poor outcomes. Advancements have been made in our understanding of the aetiologies of both conditions. Several predisposing factors linked to critical illness have been implicated in ACPO. CIPO is a functional motility disorder, historically misdiagnosed, with unnecessary surgery being performed in many patients with dire consequences. This review discusses the pathophysiology, clinical and diagnostic features, and treatment of each. For ACPO, a safer pharmacological approach to treatment is presented in a modified up‐to‐date algorithm. The importance of CIPO as a differential diagnosis when seeing patients with recurrent admissions for abdominal pain and distention is also discussed, as well as specific indications for surgery. While surgery is often a last resort, the role of the surgeon in the management of both ACPO and CIPO cannot be undervalued. By characterizing each condition in a common review, the knowledge gleaned aims to optimize outcomes for these frequently complex patients.